Phenotype and natural history of mitochondrial membrane protein-associated neurodegeneration - Iankova, Vassilena; Sparber, Peter; Rohani, Mohammad; Dusek, Petr; Büchner, Boriana; Karin, Ivan; Schneider, Susanne A; Gorriz, Juan M; Kmiec, Tomasz; Klopstock, Thomas (Brain, 2024)
Mitochondrial membrane protein-associated neurodegeneration (MPAN) is an ultraorphan neurogenetic disease from the group of neurodegeneration with brain iron accumulation (NBIA) disorders. Here we report cross-sectional and longitudinal data to define the phenotype, to assess disease progression and to estimate sample sizes for clinical trials. We enrolled patients with genetically confirmed MPAN from the Treat Iron-Related Childhood-Onset Neurodegeneration (TIRCON) registry and cohort study, and from additional sites. Linear mixed-effect modelling (LMEM) was used to calculate annual progression rates for the Unified Parkinson's Disease Rating Scale (UPDRS), Barry-Albright Dystonia (BAD) scale, Schwab and England Activities of Daily Living (SE-ADL) scale and the Pediatric Quality of Life Inventory (PedsQL). We investigated 85 MPAN patients cross-sectionally, with functional outcome data collected in 45. Median age at onset was 9 years and the median diagnostic delay was 5 years. The most common findings were gait disturbance (99%), pyramidal involvement (95%), dysarthria (90%), vision disturbances (82%), with all but dysarthria presenting early in the disease course. After 16 years with the disease, 50% of patients were wheelchair dependent. LMEM showed an annual progression rate of 4.5 points in total UPDRS. The total BAD scale score showed no significant progression over time. The SE-ADL scale and the patient- and parent-reported PedsQL showed a decline of 3.9%, 2.14 and 2.05 points, respectively. No patient subpopulations were identified based on longitudinal trajectories. Our cross-sectional results define the order of onset and frequency of symptoms in MPAN, which will inform the diagnostic process, help to shorten diagnostic delay and aid in counselling patients, parents and caregivers. Our longitudinal findings define the natural history of MPAN, reveal the most responsive outcomes and highlight the need for an MPAN-specific rating approach. Our sample size estimations inform the design of upcoming clinical trials.
Keywords: mutace; dystonie; Neurodegenerative Diseases; Phenotype; dítě; dysartrie; opožděná diagnóza; dystonické poruchy; průřezové studie; Dystonia; kvalita života; Dystonic Disorders; lidé; neurodegeneration with brain iron accumulation; Activities of Daily Living; MPAN; membránové proteiny; Mutation; mitochondriální membrány; neurodegenerativní nemoci; kohortové studie; Cohort Studies; činnosti denního života; Cross-Sectional Studies; Delayed Diagnosis; Mitochondrial Membranes; Membrane Proteins; Child; fenotyp; Dysarthria; NBIA; mitochondrial membrane protein-associated neurodegeneration; Quality of Life; Humans